STUDY OF THE CHANGE OF STEEL SURFACE TOPOGRAPHY ON A BOUNDARY LUBRICATED RECIPROCATING SLIDING CONTACT - Jamari, Jamari (ROTASI, 2010)
Experiments on ball-on-plate steel under boundary lubricated reciprocating sliding contact were performed to study the change of the surface topography. The surface characteristics were measured by an optical profilometer: Micromap 512. In order to get more detailed information about the surfaces before and after the experiment the Matching and Stitching method was employed. The profile evolutions of the surface for a certain number of running-in cycles were presented. Analysis of roughness was done to get the important information of the surface topography change. Results show that the surface changes more in the running direction than in the traverse direction.